Humane entrepreneurship and innovation : an alternative way to promote sustainable development - Botti, Antonio; Parentem Roberto (Emerald Publishing Limited, 2024)
Entrepreneurship is evolving rapidly due to positive phenomena, such as digitalization and the green transition, and negative ones, such as crises and global emergencies. In this fresh approach to the unique role entrepreneurship can play across environmental protection and social equity, leading scholars explore the world of Humane Entrepreneurship (HumEnt). Introducing a new model of entrepreneurship that considers the human side of sustainable development, they delve into elements of Entrepreneurship Orientation, Human Resource Orientation, and Sustainability Orientation, focusing on risk-taking, effective people management practices, and societal expectations. Showing how HumEnt encourages employee engagement and promotes sustainability to leave positive impacts on society, the chapter authors examine how a human-centric approach to entrepreneurship can help achieve a balance between technological advancement and societal needs. Humane Entrepreneurship and Innovation provides a framework for entrepreneurs, students, and researchers to develop sustainable innovations that benefit society as a whole. This inclusive approach encourages entrepreneurs to consider the needs of all stakeholders, including employees, customers, and the environment. The Emerald Studies in Sustainable Innovation Management series aims to explore innovation management's advancements in turbulent times, with special attention to the transition towards a sustainable economy.
Keywords: Entrepreneurship -- Moral and ethical aspects.; Sustainable development.; Business & Economics -- Entrepreneurship.; Entrepreneurship, Start-ups.; elektronické knihy; electronic books